Navigating Toward a Gender-Balanced Culture in Leadership Roles in Higher Tertiary Institutions (HTIs) - Krambia-Kapardis, Maria; Spanoudis, George (My University, 2024)
The European Commission (EC) and the United Nations advocate the importance of gender equality in their agendas and goals. More specifically, the EC has highlighted the importance of increasing women’s representation in leadership positions, yet in a minority of universities around the globe, there is a gender imbalance. By excluding women from key academic leadership roles, a culture that superficially accepts women into roles that do not challenge the hierarchy is normalized, and a rubber stamp to hegemonic masculinity is established as typical conduct. This study utilizes data from a national survey distributed across all full-time academic and administrative staff in Cyprus’s 13 universities to examine the presence of gender disparities in leadership. The survey was designed based on a comprehensive review of the literature and pilot tested by experts in the field. It was then distributed by university rectors, reaching a total of 337 respondents. The data were analyzed to confirm that the characteristics of an extremely gendered environment, as established by researchers, are found in higher tertiary institutions (HTIs). Secondly, the authors found that the disparities between the leadership skills and traits held most prominently by women in HTIs, as opposed to their male counterparts, enhance the arguments put forward toward gender balance in leadership. Thirdly, the barriers holding women back from voicing their wishes to seek leadership roles in HTIs were identified. Finally, recommendations are made on how to overcome the androgenic environment, to move the needle and have more women seek leadership positions in a culture which preserves hegemonic masculinity. Changing this culture will navigate towards a more balanced working environment for staff and students, and can thus address ethical issues in a more inclusive and gender-balanced environment.
Keywords: Gender balance; Leadership; Higher tertiary institutions